Development of China's state-controlled firms: The case of the consumer electronics sector - Hailan Yang; Stephen Lloyd Morgan (Management Revue, 2010)
The aim of the paper is to investigate the development of China's state-controlled firms in the consumer electronics sector, where we focus on the evolution of firm business strategy and ownership structure, two aspects of a firm's internal organization crucial for competitive advantage. The Chinese consumer electronics sector is used for the study, partly on the basis of its significance in national economy, but also because its growth experience is typical of many industries in the Chinese economy as a whole. This paper uses case studies to identify the specific characteristics of China's firms that operate in a transitional society undergoing social and economic transformation. It is argued in this paper that there exist different ways of development of China's state-controlled firms with different competitive position.
Keywords: 650; development; state-controlled; China; qualitative research